From gravity to water: analyzing climate change in Brazil with computational methods - Trigo, Fabian (Cadernos de Astronomia, 2025)
Predicting droughts and floods in climatically dynamic regions requires rigorous analyses that integrate both spatial and temporal information. This study leverages gravitational data from the GRACE missions to examine hydrological variability in Brazil, an area of strategic importance due to its extensive river network and high sensitivity to global climate phenomena such as El Niño and the Pacific Decadal Oscillation. By adopting a computational framework that includes Singular Value Decomposition (SVD), CFAR (peak detection), and DBSCAN (spatial clustering), key variability patterns are identified and highlight regions with elevated hydrological vulnerability, notably Manaus, Mato Grosso, and Minas Gerais.